Differential effects of antiretroviral drug toxicity in male versus female children who are HIV-exposed but uninfected. (1st January 2021) - Gilmore, Julian C.; Serghides, Lena; Bendayan, Reina
Abstract : N/A: In recent years, widespread use of antiretroviral therapy (ART) during pregnancy has been increasingly effective in reducing risk of vertical transmission of HIV, with over 80% of pregnant women living with HIV now accessing ART, and a 41% reduction in new infections in children between 2010 and 2018. Despite these strides, the developmental toxicity of widely administered antiretroviral drugs (ARVs) remains poorly described and existing literature often fails to account for fetal and infant sex as a variable. Recent reports have identified associations between in-utero exposure to commonly used antiretroviral regimens and alteration in neurodevelopment, growth, and metabolism amongst children who are HIV-exposed but uninfected, with findings of sex differences in the prevalence and severity of ARV toxicity. These differences are potentially explained by variable exposure to ARV drugs in utero or exacerbation of existing sex-linked risk factors. Fetal ARV exposure is mediated by placental and fetal drug transporters and metabolic enzymes, which may contribute to the manifestation of sex differences. Existing evidence of sex differences in ARV toxicity in fetal development is concerning, and demands further research to guide optimal treatment options for maternal health and prevention of vertical HIV transmission.